Perception of restaurateurs on the sustainability of the concept of dining out 'organically' in New Zealand - Yiu, Albert Yau Kwong (Auckland University of Technology, 2008)
Dining out ‘organically’ has become a global trend and is popular in many countries such as the United States of America (USA), Germany and Great Britain; however, it is only a niche dining concept in New Zealand. Most existing studies have focused on consumers’ attitudes and behaviours towards organic food consumption in New Zealand and very little research and literature discusses the perceptions of restaurateurs in the local organic food service industry. This study therefore seeks to explore how restaurateurs perceive the concept of dining out ‘organically’ and how they implement this innovative concept into their business operations within the local context. The areas examined in the study include the general perception of the local restaurateurs on organic dining trends, their motivation to enter the organic food service sector, their business philosophy of implementing an organic dining concept into their business operation, their future view towards organic dining trends and their perceived needs for government assistance. The study employs a qualitative approach for research investigation. Data have been collected from semi-structured interviews, then grouped and analysed to develop themes based on the principles of grounded theory. The study finds differences in the perception of the concept of dining out ‘organically’ between the two groups of samples (i.e. one high class restaurateur and four middle class restaurateurs). The high class restaurateur had no faith in the organic dining trend; he promoted only a luxury gastronomic experience and inclusion of organic ingredients into his menu had no specific meaning other than a kind of new experience to customers. However, the middle class restaurateurs were pioneers in leading the organic dining trend. They strove to be financially sustainable, while seeking every possible way to increase market awareness by promoting the benefits of eating ‘organically’. The study concludes that true organic restaurateurs not only face challenges from those who attempt to capitalise on the organic dining concept, but also the low market demands for organic dining that make it difficult for them to survive. The study recommends that the New Zealand government increases funding to the organic farming industry in order to improve organic production and organises more market awareness programmes to educate consumers about the benefits of organic eating. Thus, the study supports the view that the organic food service industry will remain as a niche market, unless the government makes more effort to support the related industries.
Keywords: Qualitative research; Hospitality industry; Organic restaurants; Organic food services; Dining trends; Sustainability